Diversity of epigeal ants (hymenoptera: Formicidae) in urban areas of alto tietê - De Souza, D. R.; Dos Santos, S. G.; De Munhae, C. B. [UNESP]; De Morini, M. S.C. (My University, 2012)
The Objective of This Stud. Was to Conduct an Inventory of the Ant Fauna, Evaluating Indicat. of Diversity, Litter Comm. Composition and Similarity among Seven Areas Located Around the City of Mogi das Cruzes (SP). in Each Area 20 Pitfalls Were Distributed, Which Remained in the Fld. for Seven Days. Four Samplings Were Performed, Two in the Rainy Season and Two during Dry Season. in Total There Were 92 Recorded Species, 36 Genera, 19 Tribes and Seven Subfamilies. the Most Frequent Species Belong to the Genera Pheidole and Camponotus, Both Com. in the Neotropics. Differences Were Observed in Species Composition with the Form. of Two Groups, One under the Influence of the Atl. Forest and Other in the Urban Reg.. only One Exotic Species, Paratrechina Longicornis, Was Recorded. the Results Indicate the Importance of the Forest Surrounding the City to Maintain the Biol. Diversity of Ant Comm.
Keywords: Anthropization; Atlantic forest; Communities; Exotic ants; Serra do itapeti